Fuzzy integrated decision support system for evaluation of student project - Norliza Ghazali
Evaluation and decision-making must take into account many factors in order to achieve the objective and targeted goal. The evaluation process is usually complicated because we have to take into account a variety of criteria, in addition to the problems that are vague and unstructured. The assessment of student project is one of the project that involved with more than one assessor is required to make a decision. The Interactive Decision Support System is then very much needed to.be developed by including the consideration of the fuzziness factors that have been raised in order to facilitate the evaluation and decision making process. The objective of this study is to propose the integrated Fuzzy Multi-Criteria Decision Making (FMCDM) models in appraising the student projects. A framework for student project evaluation has been developed using the Fuzzy Ranked Analytic Hierarchical Process (FRAHP) and Fuzzy Technique for Order Preference by Similarity to Ideal Solution (FTOPSIS). In addition, the Weighted Model is also used to evaluate the criteria involved. Next, a prototype system is developed to test the effectiveness of the framework. A feasibility study is carried out by interviewing coordinators for student projects at three (3) institutions, namely Universiti Sultan Zainal Abidin (UniSZA), Universiti Malaysia Terengganu (UMT), and Universiti Teknologi Mara (UiTM). The usability study is conducted by distributing questionnaires to lecturers that have the eX9eriences as supervisors and/or panel evaluators. In addition, a numerical test has also been performed on the developed system. The results indicate that the developed prototype is capable of addressing the problem of unstructured and complex, such as evaluation of student projects (as well as other evaluations with the same features, such research grant applications, articles for publication and tender documents). Overall, 85% of respondents have agreed with the merged model approach and are satisfied with the developed system. As for the conclusion, DSS that is based on the integrated model approach needs to be adopted in academic management in enhancing the academic quality and its success.